Analysis of the Need for Mathematics Teaching Materials "Digital Comic Based on Islamic Values" for Class X SMA Students in Era 5.0 - Niswatun Hasanah; Mohammad Syaifuddin; Rani Darmayanti; Akhsanul In’am (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
In modern Industrial Technology 5.0, educators are challenged to develop the ability to create learning media for use with technology support. Comics are very popular among teenagers, including high school students. One type of comic is digital comics, which was once a global trend that served as an effective learning medium. This type of research is research and development (R & D) using 3D research methods (definition, design, development). In this study, researchers were limited to the definition stage. The equipment used in this study was a questionnaire to analyze the needs of Class X teachers and students and nine math teachers in MAN2 Malang. Based on the results of the survey conducted, it can be concluded that students need digital comic learning media based on Islamic values ​​of inverse functional materials. This is based on data that 81.7% of respondents strongly agreed and 83.5% of teachers strongly agreed that it was necessary to develop digital comic learning media based on Islamic values ​​in order to motivate them to learn